Comparison of questionnaire and clinician-based assessment of Prakriti/body constitution in young adults: an observational study - Khuntia, Bharat Krushna; Rathore, Shubhangi; Sharma, Vandana; Rani, Avantika; Agarwal, Aman; Rengarajan, Krishnaveni; Upadhyay, Ashish Datt; Jat, Mansingh; Madhu, Nath; Velpandian, T.; Sharma, Gautam (International Journal Of Community Medicine And Public Health, 2024)
Background: Ayurveda emphasizes a personalized medicine approach based on Prakriti (body constitution) assessment which involves morphological observation and detailed history of physiological, behavioural, and psychological attributes. In Ayurveda research, two commonly used prakriti questionnaires are developed by CSIR (Q1) and CCRAS (Q2). These questionnaires are presumed to have similar predictive capabilities, but no study has compared them with the clinician-based prakriti assessment method for suitability in clinical settings. This study aimed to compare Q1, Q2, and their agreement levels with the clinician-based prakriti assessment (CPA) method. Methods: This observational study was conducted from July 2022 to January 2023, involving adults of both sexes aged aged 18-35 years. Upon obtaining written informed consent, trained Ayurvedic clinicians assessed the prakriti of all participants using Q1, Q2 and CPA methods. Results: Out of 138 participants recruited, 67% were female. The mean±SD age for males and females was 27.80±4.43 and 26.58±4.56, respectively. Mixed prakriti types were more common than predominant types among participants. The CPA method substantially agrees with Q1 (Cohen’s kappa=0.75) and moderately agrees with Q2 (Cohen’s kappa=0.59). The positive predictive value ranges for Q1 and Q2 were (46.2-100%) and (48-100%), respectively. Conclusions: Q1 and Q2 are consistent with the CPA method, with Q1 showing better agreement. Further studies including other questionnaires is required to validate the results.